Organic charge-modulated transistor for electrophysiological measurements of human-derived neurospheroids - Terranova, Fabio; Viola, Fabrizio Antonio; Di Lisa, Donatella; Massobrio, Paolo; Martinoia, Sergio; Bonfiglio, Annalisa; Spanu, Andrea (Frontiers in Bioengineering and Biotechnology, 2025)
In this work, we present an alternative system to standard microelectrode arrays for monitoring the electrical activity of 3D cellular aggregates such as neurospheroids, which are known to better replicate the complex architecture and cellular interactions of native neural tissue than 2D cultures. The system is based on an ultra-sensitive organic sensor called Organic Charge-Modulated Field Effect Transistor (OCMFET) fabricated through low-resolution, low-cost fabrication techniques. This peculiar organic charge sensor offers interesting features like the absence of a reference electrode in the culture medium, a direct charge amplification, mechanical flexibility, and optical transparency. As a preliminary validation, the OCMFET system has been coupled to rtTA/Ngn2-positive human induced pluripotent stem cell (hiPSC)-derived neurospheroids and was able to reliably detect their spontaneous electrical activity exhibiting a high SNR. This preliminary validation lays the foundation for the development of simple, low-cost, and ultra-flexible organic transistor-based systems for high-performing, reliable interfacing with 3D neuronal structures.